Modification of CVR / IT Software Project Management Methodology on Outsourced Applied Research to Internship Program Environment - Renan Prasta Jenie (ComTech: Computer, Mathematics and Engineering Applications, 2010)
This study is done to analyze how to Internship Student can be used by Tech Dev as a Research Outsourcing Body, what to tweak and modify. It is suggested to use CVR / IT Model on Research Project Management System Utilization. The model is implemented in system procedures. Based on observation until 2009, the system adoption rate is 40 % at most.